Design and synthesis of the honeycomb PtSnNa/ZSM‐5 monolithic catalyst for propane dehydrogenation. (9th December 2019) - Tong, Qing; Zhao, Shiyong; Liu, Yubing; Xu, Bolian; Yu, Lei; Fan, Yining
Abstract : A novel PtSnNa/ZSM‐5 monolithic catalyst was designed and synthesized for the propane dehydrogenation reaction, which was a significant transformation in industry. Experimental results showed that although the propane conversion and the propylene selectivity gradually fell down along with the reaction time, the descent speed of the PtSnNa/ZSM‐5 monolithic catalyst was slower than that of the granule catalyst and the propane conversion and propylene selectivity of the reaction with monolithic catalyst still remained at a high level after 12 hr. The monolithic catalyst had regular pore structure that facilitated the separation of the product from the catalyst and reduced the limitation on internal and external diffusion and mass transfer, and led to the high catalytic activity and stability. The catalyst could be easily fabricated and was of highly industrial application potential. Abstract : A novel honeycomb PtSnNa/ZSM‐5 monolithic catalyst was designed and prepared for propane dehydrogenation to produce propylene.